IV Nembutal: Safe Sedation for Children Undergoing CT - Strain, John D.; Campbell, John B.; Harvey, Lee A.; Foley, L. Christopher (American Journal of Neuroradiology, 1988)
In a prospective study of 225 consecutive pediatric patients who required sedation for CT imaging, we monitored oral and nasal air flow, transcutaneous oxygen saturation, and cardiac rate and rhythm before and after the administration of IV Nembutal. In addition, the first 50 patients in this series had blood pressures mechanically monitored at 1-min intervals. There was no significant change in the cardiac rate, rhythm, or blood pressure in any patient. Seventeen episodes (7.5%) of transient oxygen desaturation to 80% of baseline or less occurred after sedation. The patterns of oxygen desaturation in this series can be explained by the following mechanisms: (1) hyperventilation leading to hypocapnia with resultant loss of the CO2 stimulus of respiration (12 patients); (2) upper airway obstruction from pharyngeal muscle relaxation (three patients); (3) a shift in sensitivity of CNS CO2 receptors (one patient); and (4) central apnea (one patient). Oxygen desaturation normalized spontaneously in 14 patients. In two patients, oxygen saturations returned to normal after modification of head position to optimize airway patency. In one patient, mild stimulation was required to interrupt transient apnea, All but one patient in whom desaturation occurred showed oxygen desaturation within the first 5 min after IV sedation. At The Children's Hospital of Denver, IV Nembutal has been used in over 870 pediatric patients. No patient required resuscitation, intubation, or assisted ventilation. Only one patient required prolonged observation, and one patient demonstrated an idiosyncratic hyperactive response. The sedation failure rate was less than 1%. The average dose of sedation was reduced when compared with 1M Nembutal because the rapid onset of activity after IV administration allowed titration of dose to patient response.